A formação do Professor de Línguas de uma Perspectiva Sociocultural - Abrahão, Maria Helena Vieira [UNESP] (Universidade Estadual de Londrina, 2012)
With the development of cognition studies and the awareness that teachers’ previous experiences, knowledge acquired in language teacher education programs and classroom experiences in different contexts shape the ways teachers think and construct their teaching practices, teacher education programs start to understand, from a sociocultural perspective, teachers’ learning as a dialogic process of knowledge co-construction, which is situated and emerges from practices and sociocultural contexts. Considering the relevance of this new perception, this article aims at presenting such theoretical perspective as well as its contributions to language teacher education research and teaching.

Com o desenvolvimento de estudos sobre cognição e o reconhecimento de que as experiências prévias dos professores, o conhecimento adquirido em cursos de formação e as experiências de sala de aula em diferentes contextos moldam as maneiras como os docentes pensam e constroem suas práticas, os programas de formação de professores passam a ver, de uma perspectiva sociocultural, a aprendizagem docente como um processo dialógico de coconstrução de conhecimentos que é situado e emerge da participação em práticas e contextos socioculturais. Considerando a relevância desse novo olhar, este artigo tem por objetivo apresentar tal perspectiva teórica, bem como suas contribuições para a pesquisa e o ensino na área de formação de professores de línguas.
Language teacher education from a sociocultural perspective
Keywords: Formação de professores de línguas; Perspectiva sociocultural; Aprendizagem docente; Language teacher education; Sociocultural perspective; Teacher learning